HUBUNGAN PENGETAHUAN DASAR KONSTRUKSI KAYU DENGAN HASIL BELAJAR PRAKTEK KERJA BANGKU DI SMKN 58 JAKARTA - Hasty Wulandari; Daryati Daryati; R Karsono (LPPM Universitas Negeri Jakarta, 2015)
This study aims to explore relations in the knowledge base for thr theory and application of work practieson the bench so asto create the correspondence between the basic knowledge learned by practice to be implemented, therefore students need to get enough stock in the understanding of the sciences that are taught in subjects construction Work bench Wood and Practice.In this research, conducted research at the SMKN 58 Jakarta by using quqsy experimental method, and the sample consisted of class X Program Wood Constructions Engineering Expertise as many as 31 students. Instruments used in this study is a test. These instruments use objective tests with four alternative answers to 30 questions. Aspects are measured in this testknowledge, while for measuring the value of work practice used bench practice that has been done by the class X Program Technical Expertise in Wood Construction SMKN 58 Jakarta. Once the instrument is made then tested the validity and reliabilityof the students outside of the sample, because the studied samples in the selected schools to test the validity and reliability SMKN 1 Cibinong, after the validity and reliability analysis was then performed grain matter and techniques of data analysis, data analysis techniques used in this study is regression.Based on the studies indicates that there is a positive relations between the Knowledge Base Construction Wood Bench Practice Learning Outcomes. The degree of association between variables Knowledge Base Construction Wood Bench Work Practice Learning Outcomes can be seen from the value of the correlation coefficient (rxy) of 0.470. This illustrates that the relations between the Knowledge Base Construction Wood Bench Work Practice Learning Outcomes are linked. Knowlwdge Base Construction Wood only slightly contribute to the high and low result Intern Learning Bench, that means the higher the Knowledge Base Wood Construction students, the higher the bench Work Practice Learning Outcomes